(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Today, diabetic retinopathy is one of the social diseases that worries the whole world 5% of people on earth suffer from diabetes. 60,000 new patients are registered annually. More than 1,000,000 diabetics will lose their legs. Diabetic retinopathy is diagnosed in every 5 patients with diabetes mellitus. The development of modern technologies, low mobility, non-compliance with a healthy lifestyle leads to an increase in the number of complications of this disease.